Honey and Nigella sativa against COVID‐19 in Pakistan (HNS‐COVID‐PK): A multicenter placebo‐controlled randomized clinical trial. (24th November 2022) - Ashraf, Sohaib; Ashraf, Shoaib; Ashraf, Moneeb; Imran, Muhammad Ahmad; Kalsoom, Larab; Siddiqui, Uzma N.; Farooq, Iqra; Akmal, Rutaba; Akram, Muhammad Kiwan; Ashraf, Sidra; Ghufran, Muhammad; Majeed, Nighat; et al.
Abstract: Until now, no specific and effective treatment exists for coronavirus disease 2019 (COVID‐19). Since honey and Nigella sativa (HNS) have established antiviral, antibacterial, antiinflammatory, antioxidant, and immunomodulatory properties, we tested their efficacy for this disease in a multicenter, placebo‐controlled, and randomized clinical trial at four medical care facilities in Pakistan. RT‐PCR confirmed COVID‐19 adults showing moderate or severe disease were enrolled in the trial. Patients were randomly assigned in a 1:1 ratio to receive either honey (1 g kg −1  day −1 ) and Nigella sativa seeds (80 mg kg −1  day −1 ) or a placebo for up to 13 days along with standard care. The outcomes included symptoms' alleviation, viral clearance, and 30‐day mortality in the intention‐to‐treat population. Three hundred and thirteen patients, 210 with moderate and 103 with severe disease, underwent randomization from April 30 to July 29, 2020. Among the moderate cases, 107 were assigned to HNS, whereas 103 were assigned to the placebo group. Among the severe cases, 50 were given HNS, and 53 were given the placebo. HNS resulted in ~50% reduction in time taken to alleviate symptoms as compared to placebo (moderate cases: 4 vs. 7 days, Hazard Ratio [HR]: 6.11; 95% Confidence Interval [CI]: 4.23–8.84, p  < 0.0001 and for severe cases: 6 vs. 13 days, HR: 4.04; 95% CI: 2.46–6.64; p  < 0.0001). HNS also cleared the virus earlier than placebo in both moderate cases (6 vs. 10 days, HR: 5.53; 95% CI: 3.76–8.14, p  < 0.0001) and severe cases (8.5 vs. 12 days, HR: 4.32; 95% CI: 2.62–7.13, p  < 0.0001). HNS further led to a better clinical score on day 6 with normal activity resumption in 63.6% vs. 10.9% among moderate cases (OR: 0.07; 95% CI: 0.03–0.13, p  < 0.0001) and hospital discharge in 50% versus 2.8% in severe cases (OR: 0.03; 95% CI: 0.01–0.09, p  < 0.0001). In severe cases, the mortality rate was less than 1/4th in the HNS group than in placebo (4% vs. 18.87%, OR: 0.18; 95% CI: 0.02–0.92, p  = 0.029). No HNS‐related adverse effects were observed. HNS, compared with placebo, significantly improved symptoms, expedited viral load clearance, and reduced mortality in COVID‐19 patients. This trial was registered on April 15, 2020 with ClinicalTrials.gov Identifier: NCT04347382.